Microcellulose From Pineapple Leaf Fiber as a PotentialSustainable Material: Extraction And Characterization - Nawangsari, Putri; Fatra, Warman; Kusuma, Aryandi; Badri, Muftil; P.C1, Dedi Rosa; Masnur, Dedy (Politeknik Negeri Lhokseumawe, 2024)
Pineapple leaf fiber is consideredan agricultural waste during the harvesting process. Pineapple leaves are rich in cellulose, which made it applicable in many industrial applications. This study aims to extract and characterize microcellulose from pineapple leaf waste in Kampar district, Riau. Pineapple fibers were isolated by alkalization (5 % NaOH) at 70 ºC for 150 minutes, followed by bleaching treatment(3% H2O2) at 60°C for 60minutes. Microcellulosewascharacterized through various techniques, namely chemical composition analysis, Fourier transform analysis (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (DT/TGA). The results reveal that the extractedmicrocellulose has significantcellulose content (72.45%) with a crystallinity index of 73.48%. The FTIR spectra of microcellulose indicatethat alkalization and bleaching treatments removed lignin and hemicellulose in varying degrees. Moreover, the extracted microcelluloseshows high thermal stability, the maximum decompositionoccurredat 347 ºC (weight residue 16.37%).Pineappleleaf fiber in Kampar district, Riau, can be a source of microcellulose as a renewable, eco-friendly, and sustainable material for future industrial applications.